2020
DOI: 10.23926/rpd.2526-2149.2020.v5.n2.p1191-1210.id766
|View full text |Cite
|
Sign up to set email alerts
|

Coronavírus Em Memes: Potencialidades Pedagógicas De Ler Em Ciências

Abstract: Este artigo objetiva discutir as Tecnologias Digitais (TD) e sua utilização na sala de aula, ressaltando o papel dos memes como um potencial pedagógico para abordar temas da atualidade como o Coronavírus. Para isso, efetuou-se pesquisas em artigos científicos e análise de memes compartilhados em redes sociais. Os memes analisados dizem respeito às temáticas: morfologia do vírus, disseminação, sintomas da doença, higiene pessoal, grupo de risco e relação com outras doenças. Identificou-se que os memes possuem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…According to Santos et al (2020, p. 6), there is a "[...] scarcity of academic productions that encourage discussions regarding the topic addressed [...]" in Chemistry teaching. On the other hand, some productions, such as those by Simplício et al (2020), deal with the pedagogical potential of memes to discuss current topics, such as Coronavirus. Oliveira (2020, p. 13), collaborating with research in the area, argues that memes, in Science classes, "[...] linked to scientific dissemination, [...] can be a way of expression of a collective authorship by users in a network, connected to the displacement of the science language dissemination and popularization".…”
Section: Memes and The Natural Science Teachingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Santos et al (2020, p. 6), there is a "[...] scarcity of academic productions that encourage discussions regarding the topic addressed [...]" in Chemistry teaching. On the other hand, some productions, such as those by Simplício et al (2020), deal with the pedagogical potential of memes to discuss current topics, such as Coronavirus. Oliveira (2020, p. 13), collaborating with research in the area, argues that memes, in Science classes, "[...] linked to scientific dissemination, [...] can be a way of expression of a collective authorship by users in a network, connected to the displacement of the science language dissemination and popularization".…”
Section: Memes and The Natural Science Teachingmentioning
confidence: 99%
“…Over the last few decades, research in the area of Natural Sciences (Chemistry, Physics and Biology) has demonstrated concerns about the teaching offered in school spaces (Alves et al, 2021;Simplício et al, 2020) and the way in which the contents have been addressed in entrance exams in higher education (Hernandes;Martins, 2013;Schneider;Scheid;Boer, 2021). These studies reinforce the need to reflect and discuss teaching and learning processes that provide the opportunity for the development of "[...] thinking capabilities, in order to acquire knowledge to understand scientific debates, issues related to technology, and understanding the complex interactions involving Science and Society" (Teixeira, 2019, p. 851).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao longo das últimas décadas, pesquisas na área de Ciências da Natureza (Química, Física e Biologia) têm demonstrado preocupações com o ensino ofertado nos espaços escolares (Alves et al, 2021;Simplício et al, 2020) e com a forma como os conteúdos vêm sendo abordados nos processos seletivos de ingresso no ensino superior (Hernandes;Martins, 2013;Schneider;Scheid;Boer, 2021). Esses estudos reforçam a necessidade de refletir e discutir processos de ensino e aprendizagem que oportunizem o desenvolvimento de "[...] capacidades de pensamento, no sentido de ocorrer uma aquisição do conhecimento para o entendimento de debates científicos, de questões ligadas à tecnologia, e de compreensão das interações complexas envolvendo Ciência e Sociedade" (Teixeira, 2019, p. 851).…”
Section: Introductionunclassified
“…Em Ciências da Natureza, por exemplo, alguns pesquisadores, como Alves et al (2021) e Simplício et al (2020), analisam o meme enquanto recurso didático, observando, com isso, a sua potencialidade para a abordagem de temas da Química e da Biologia, respectivamente. Nesse sentido, "[...] os memes têm demonstrado cada vez mais seu potencial como recursos didáticos no ensino das diversas disciplinas e desta forma se consolidado como importante recurso na prática docente" (Alves et al, 2021, p. 813).…”
Section: Introductionunclassified